Priority and random selection for dynamic window secured implicit geographic routing in wireless sensor network - Mohd Hanapi, Zurina; Ismail, Mahamod; Jumari, Kasmiran (Science Publications, 2009)
Problem statement: Sensor nodes are easily exposed to many attacks since it were deployed in unattended adversarial environment with no global addressing and used for critical applications such as battlefield surveillance and emergency response. While the sensor also needs to act as a router to relay a message to a required recipient, then this increased the vulnerabilities to a network layer. However, existing security mechanisms are not permissible to be fitted directly into any sensor network due to constraints on energy and computational capabilities of sensor node itself that require on the modification on the protocols that associated with the sensor node itself in order to provide the security. Approach: In this study, a Dynamic Window Secured Implicit Geographic Forwarding (DWIGF) routing protocol was presented which based on an approach of lazy binding technique and dynamic time on collection window and inherits a geographical routing techniques. Results: The DWIGF was intelligent to minimize a Clear To Send (CTS) rushing attack and robust against black hole and selective forwarding attacks with high packet delivery ratios because of selection of a failed node and an attacker was minimized respectively. Moreover, few routing attacks were eliminated since the routing technique used was classified as geographic routing. Conclusion: This novel routing protocol was promising a secured routing without inserting any existing security mechanism inside.